Pharmacogenetics: an Emerging Therapeutic option for Bangladesh - Ahmed, Maizbha Uddin (Dhaka University Journal of Pharmaceutical Sciences, 2015)
From socioeconomic point of view adverse drug reactions (ADRs) present a challenging and expensive public health problem worldwide. Most important factors involved in this life threatening events are false diagnosis, failure of treatment, lack of proper patient counseling, lack of knowledge regarding medication use and polypharmacy. Pharmacogenetic research explores genetic variability between patients to explain observed differences in effectiveness of a drug therapy as well as adverse event profile. Thus, pharmacogenetic testings could help to prevent treatment failure and adverse drug reaction in patients. It also allows the detection and prediction of ADRs and is a tool that can reduce the risks associated with ADRs. In this particular review we will discuss how genetic variation can influence drug response and how personalized medicine can be achieved as well as some recent pharmacogenetic works carried out in Bangladesh. The aim of this review is to increase awareness of the physicians and other health care practitioners and professionals about the variation of drug response due to genetic variation. This review can help the physicians to identify genetic factors associated with ADRs with all drugs and effectively incorporate pharmacogenetics into the practice of pharmacovigilance. DOI: http://dx.doi.org/10.3329/dujps.v13i2.21902 Dhaka Univ. J. Pharm. Sci. 13(2): 207-214, 2014 (December)